The Paradox of Academic Stress in the Digital Age: A Comparative Analysis of Academic Social Comparison and Digital Self-Regulation in University Students - Muhammad Al Fikhri; Ifdil Ifdil; Fricha Meivilona Yendi; Soeci Izzati Adlya; Ade Herdian Putra (Universitas Negeri Padang, 2025)
Academic stress is commonly experienced by university students and is increasingly influenced by the dynamics of campus digitalization. This study aims to analyze the effect of academic social comparison and digital self-regulation on academic stress. The method used is a correlational quantitative approach with multiple regression on 256 university students selected through cluster random sampling. The instruments used are three five-point Likert scales. Data were collected online and analyzed through classical assumption tests and multiple regression. The results showed that the regression model was not significant (R² = 0.000; p = 0.975), with academic social comparison (p = 0.912) and digital self-regulation (p = 0.847) having no effect on academic stress. These findings differ from previous studies and suggest that other factors may be more dominant. The implications of this study emphasize the need for a multidimensional approach in understanding student stress and the development of more comprehensive and contextual counseling services.